2013
DOI: 10.1371/journal.pone.0068422
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Roles of SDF-1α and EGF Gradients on Tumor Cell Migration Revealed by a Robust 3D Microfluidic Model

Abstract: Chemokine-mediated directed tumor cell migration within a three dimensional (3D) matrix, or chemoinvasion, is an important early step in cancer metastasis. Despite its clinical importance, it is largely unknown how cytokine and growth factor gradients within the tumor microenvironment regulate chemoinvasion. We studied tumor cell chemoinvasion in well-defined and stable chemical gradients using a robust 3D microfluidic model. We used CXCL12 (also known as SDF-1α) and epidermal growth factor (EGF), two well-kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 46 publications
6
98
1
Order By: Relevance
“…Zaman et al observed DU-145 prostate carcinoma cells migrating in ECMs with varying stiffness and adhesion molecule density, and concluded that cell migration speed in this system was dependent on the balance between ECM stiffness and adhesion. Both types of migration have been observed in most tumor types, including breast, prostate, and skin cancers [1]; tumor cells are not committed to a specific migration phenotype, but rather switches between the two depending on microenvironmental factors [54,55]. For example, total MMP inhibition can transform tumor cells from mesenchymal into amoeboid phenotypes in both 3D culture and animal models [53].…”
Section: Modes Of Cell Migration In 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaman et al observed DU-145 prostate carcinoma cells migrating in ECMs with varying stiffness and adhesion molecule density, and concluded that cell migration speed in this system was dependent on the balance between ECM stiffness and adhesion. Both types of migration have been observed in most tumor types, including breast, prostate, and skin cancers [1]; tumor cells are not committed to a specific migration phenotype, but rather switches between the two depending on microenvironmental factors [54,55]. For example, total MMP inhibition can transform tumor cells from mesenchymal into amoeboid phenotypes in both 3D culture and animal models [53].…”
Section: Modes Of Cell Migration In 3dmentioning
confidence: 99%
“…In the context of chemokine-mediated tumor cell invasion, specific chemokine-receptor pairs have associated with the invasion and metastasis of specific tumor cells. The chemokine (C-X-C motif) ligand 12 and its receptor CXCR4 are well documented to help drive metastasis of breast cancer, glioblastoma, and others, and CXCR4 expression has been associated with cancer stem cells [3,55,73]. The most widely used model system to study tumor cell response to chemokine gradients (i.e., chemotaxis) is the Boyden chamber [1,74], which is typically in the form of porous culture inserts with pore sizes that allow cell transmigration (8 um) and a chamber beneath containing other cells or chemokines [see Fig.…”
Section: Modes Of Cell Migration In 3dmentioning
confidence: 99%
“…The fiber network aligns, stiffens, and sometimes, undergoes permanent changes when subjected to strain (14, 15). These adaptive mechanical properties of the fiber network provide cells entry points to modify their local microenvironment (16-18) and as such, perform physiologically realistic functions (1,3,(19)(20)(21)(22)(23). It has been reported that the nonlinear elasticity of fibrous matrices enables cells to transmit forces over distances of hundreds of micrometers, facilitating long-range communication between individual cells (24-26) and between tumor spheroids (27).…”
mentioning
confidence: 99%
“…This is partly due to the inability of 2D cancer models to recapitulate the microenvironment of a tumor which exists in the human body. Past studies have demonstrated a significant difference in cell behavior between 2D and 3D models, specifically in terms of protein expression [2] and gradient profiles [3] , drug response [4,5] , as well as cell migration [6] , morphology [7] , proliferation [8] and viability [7] . Cell-cell and cell-matrix interactions are enhanced in 3D models compared to 2D, offering a more physiologically-relevant microenvironment.…”
Section: Clinical and Pharmaceutical Need For Threedimensional (3d) Tmentioning
confidence: 99%